Effects of co-composting of lincomycin mycelia dregs with furfural slag on lincomycin degradation, maturity and microbial communities. (October 2018) - Ren, Shengtao; Guo, Xiali; Lu, Aqian; Guo, Xiaoying; Wang, Yan; Sun, Guoping; Guo, Weiwei; Ren, Chaobin; Wang, Lianzhong
Graphical abstract: Highlights: Feasibility of co-composting of LMDs with furfural slag was evaluated. The lincomycin concentration was reduced 99% after 66 days composting. LMDs can increase the abundance and diversity of bacteria in the compost. The bacterial communities were strongly affected by the residual lincomycin. Three genera were found to be the potential bacteria to degrade lincomycin. Abstract: This paper investigated the effect of co-composting of lincomycin mycelia dregs (LMDs) with furfural slag on the degradation of lincomycin, maturity and microbial communities. Results showed that after 66 days composting, the concentration of lincomycin was removed above 99%. The final pH, C/N and germination index (GI) all met the national standards in maturity. Enumeration of total cultivable microbes showed the composting process was not inhibited by the addition of LMDs. Microbial diversity suggested that co-composting was beneficial to increase the abundance and diversity of bacterial communities for LMDs' treatment. Canonical correlation analysis (CCA) indicated the bacteria communities were strongly affected by residual lincomycin, with lincomycin reduced greatly, microbial communities of T and CK became similar at the end of composting. The potential bacteria to degrade lincomycin were Anaerococcus, Peptostreptococcus, and Lactobacillus . Based on these results, this research indicated that the co-composting was a feasible treatment for LMDs.